Convenience and Child Preference Drive Kathmandu Valley Caregivers to Choose Commercial Snack Foods for Their Children Aged 12-23 months. - Sharma, Nisha. (Tufts University. Tisch Library., 2019)
This poster aimed to identify factors that influenced caregivers's choice of commercial snack foods for their children 12-23 months.; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy